Insights into HONO sources from observations during a solar eclipse. Issue 6 (30th July 2021) - Singh, Ajit; Crilley, Leigh R.; Pope, Francis D.; Bloss, William J.
Abstract : Nitrous acid (HONO) is a key precursor to the principal atmospheric oxidant OH. HONO measurements during a solar eclipse show little variation, implying the main HONO sources are photolytic, approximately balancing removal through photolysis. Abstract : Nitrous acid (HONO) is a major, and often the dominant, precursor to primary OH radical production in the daytime boundary layer, driving the removal of many primary pollutants and formation of secondary species such as ozone and many aerosol components. A number of photochemical HONO production mechanisms have been proposed, alongside homogeneous gas-phase reactions, to account for field observations of daytime HONO. The range of production mechanisms show varying dependencies upon precursor species such as NO2, available surfaces for heterogeneous reactions, and dark/photoenhanced aspects. Here, we exploit measurements of HONO and related species during a near-total solar eclipse as a natural perturbation to the atmospheric photochemistry to assess the characteristics of the production mechanisms occurring at an urban background location. Little variation in HONO abundance was observed in response to changing light levels during the eclipse, pointing to relatively balanced photochemical source and (well-understood) sink terms. We employ a series of simple kinetic simulations to explore the consistency of different potential source mechanisms with the observations, finding evidence for a dominant role for photochemical processing of traffic-derived NO2 upon surfaces producing HONO, alongside indications of a smaller contribution from direct vehicular emissions. Other mechanisms involving dark heterogeneous reactions were not, in isolation, consistent with the observations. The critical role of NO2, ultimately derived overwhelmingly from local road traffic emissions at this location, points to significant future reductions in daytime HONO production with vehicle fleet evolution and reduction of tailpipe emissions.